PEMBINAAN KINERJA GURU OLEH KEPALA SEKOLAH DI SMA 3 LANGGAM KABUPATEN PELALAWAN PROVINSI RIAU - JURNIATI JURNIATI (LP2MTBM MAKARIOZ, 2021)
Quality education really needs professional education staff, to make school principals who are professional and have good managerial skills, the role of school principals is needed in fostering, guiding and directing teachers. A school principal must have the ability to lead a school, especially managerial abilities. The principal is a professional official in the school organization whose job is to manage all organizational resources and work together with teachers in educating students to achieve educational goals and understand all school needs. Types of school action research. The research location was at SMA Negeri 3 Langgam, Pelalawan Regency. Observation and questionnaire data collection techniques. Data analysis techniques use percentages. The results of the study illustrate that using the school principal's monitoring and evaluation method can improve teacher performance in carrying out learning tasks at school. Based on the aspects assessed in cycle I, there are still several indicators that have not been implemented by the principal. supervision, the assessment carried out in cycle II gave better results because there were already many school principals who carried out managerial performance activities, in this case there were actually no school principals who were lazy sometimes, they did not understand the work to be done so many tasks were related to performance appraisal is not going well.